Quantum Integration Model for Religion and Science - Soleh, Achmad Khudori (Afkar: Jurnal Akidah dan Pemikiran Islam, 2023)
The integration of religion and science has not been fully developed. Several models of integrating religion and science seem to contain fundamental weaknesses. This article aims to discuss an alternative integration called quantum integration. This research is a literature review using content analysis based on primary sources. The research results show that quantum integration consists of three structures: the principle of the unity of religion and science, an open attitude between scientists and religious leaders, and theistic values. This integration structure encapsulates three fundamental principles and three philosophical constructs. The three fundamental principles in question are the principle of non-contradictory between religion and science, equality, and mutual need. The three philosophical constructs consist of an un-materialistic worldview, a unified source of knowledge, openness, and theistic values. Based on its principles, philosophical construction, and structure, quantum integration can create a solid and balanced integration of religion and science that contains divine values. Quantum integration can fill in the gaps in previous models of integration of religion and science.